The investigation of a patient with unexpected venous thrombosis. Issue 842 (December 1995) - Wilde, J. T.
Abstract : Over recent years a number of hereditary and acquired defects of the circulation's natural anticoagulant mechanisms have been characterised and shown to predispose affected individuals to thrombosis. It is important to attempt to diagnose a thrombophilia state in patients with a thrombotic tendency in order to provide appropriate management, especially during at-risk situations, both for themselves and asymptomatic relatives identified through family studies. This review defines the patients who should be investigated for an underlying thrombophilia state and describes the hereditary and acquired disorders which should be screened for within an investigation profile. The recently identified factor V Leiden mutation which appears to be the most common hereditary cause of a thrombotic tendency is described in detail and descriptions of the more established thrombophilia states are included. Although the factor V Leiden mutation accounts for a significant proportion of cases fulfilling the criteria for thrombophilia screening, a predisposing cause for thrombosis remains unidentifiable in a large number of patients making it likely that over the years to come new thrombophilia states will continue to be identified.